Peptides from gluten digestion: A comparison between old and modern wheat varieties - Prandi, Barbara; Tedeschi, Tullia; Folloni, Silvia; Galaverna, Gianni; Sforza, Stefano (Food research international, 2017)
Coeliac disease is an autoimmune enteropathy that develops in genetically predisposed subjects after the ingestion of gluten or related proteins. Coeliac disease has an increasing incidence in the last years in western countries and it has been suggested that wheat breeding might have contributed to select more toxic forms of gluten. In this work, we analysed gluten peptides generated by in vitro digestion of different old and modern Triticum varieties, using LC-MS. We concluded that old varieties analysed produced a higher quantity of peptides containing immunogenic and toxic sequences than modern ones. Thus old wheat lines are not to be considered “safer” for subjects that are genetically predisposed to celiac disease. [Display omitted] •Old and modern Triticum varieties were submitted to in vitro digestion.•Peptides containing CD epitopes were quantified in all samples with LC-MS.•Statistical analysis of the data allowed comparing the different varieties.•Old wheat varieties produced a higher amount of peptides containing immunogenic and toxic sequences.•Peptide profiles were similar between modern and old Triticum varieties.